Students’ Perception of Oral Corrective Feedback in Speaking Class - Rizal, Af Rizal; wati, Ros wati; Diana, Nur Diana; Faisal, Muhammad Faisal (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
This study sought to examine students' perceptions of oral corrective feedback in speaking activities. Instructors used vocal corrective criticism in the classroom, particularly during speaking sessions. Offering vocal comments in the classroom facilitated students' proficient and accurate use of English. The study methodology used a quantitative descriptive approach, with data processed using SPSS version 23 and Microsoft Excel. Data was gathered via the distribution of a questionnaire to examine students' perceptions. Questionnaires were administered to 31 students in the fourth semester of the English Education Department as the study sample. The results indicated that the students achieved a score of 76% after data analysis using SPSS 23, reflecting a good view of oral corrective feedback in the speaking lesson. Another investigation revealed that the students agreed to offer oral corrective criticism during the speaking lesson